Marker-based analysis of genetic diversity in common bean - Singh, S.; Gutiérrez, A.; Urrea, C.; Koenig, R.; Nodari, R.; Gepts, Paul L. (1990)
Genetic diversity of common beans is presented for subdivisions of Mesoamerican groups. Three subgroups were identified by means of molecular markers, such as proteins (phaseolin) and allozymes.